Factors Associated With Hospital Readmissions Among U.S. Dialysis Facilities. Issue 2 (29th March 2022) - Paulus, Amber; Baernholdt, Marianne; Kear, Tamara; Jones, Terry; Thacker, Leroy
ABSTRACT: Introduction: The Centers for Medicare and Medicaid uses the standardized readmission ratio (SRR) to evaluate 30-day readmissions among dialysis providers in the U.S. Readmissions among dialysis recipients remains 37%. This study investigates associations among dialysis facilities and patient characteristics with facility's performance on the SRR. Methods: Descriptive, longitudinal, approach using multivariate regression analysis on data retrieved from the Dialysis Facility Report to evaluate the associations between facility-level (staffing, profit status, chain membership, clinic size, care, length of care, vascular access type, glomerular filtration rate (GFR), creatinine, hemoglobin, use of erythropoietin-stimulating agent, albumin, and primary dialysis modality) with the SRR. Results: Factors associated with a high SRR included nurse ratios, facility average GFR, and Northeast geographic location. Factors associated with a low SRR included patient care technician ratio, length of predialysis nephrology care, initiation of dialysis with an arteriovenous fistula, average hemoglobin, and Western geographic location. Conclusions: This study defines the influence predialysis nephrology care has on dialysis facilities SRRs. Access to care, adequate preparation for dialysis, and transitional support affect facilities' performance; however, without an appropriate staffing model, dialysis facilities may continue to struggle to reduce readmissions.